Italian Multicenter Registry of Bare Metal Stent Use in Modern Percutaneous Coronary Intervention Era (AMARCORD): A multicenter observational study. Issue 3 (21st March 2020) - Giannini, Francesco; Pagnesi, Matteo; Campo, Gianluca; Donahue, Michael; Ferri, Luca A.; Briguori, Carlo; Stefanini, Giulio G.; Scardala, Raffaele; Sardella, Gennaro; De Rosa, Salvatore; Figini, Filippo; Monello, Alberto; et al.
Abstract: Objectives: We aimed to evaluate the use of bare metal stent (BMS) implantation in current percutaneous coronary intervention (PCI) era, focusing on indications for use and clinical outcomes. Background: Limited data on BMS usage in current clinical practice are available. Methods: All patients who underwent PCI with at least one BMS implantation in 18 Italian centers from January 1, 2013 to December 31, 2017, were included in our registry. Rates of BMS use and reasons for BMS implantations were reported for the overall study period and for each year. Primary outcomes were mortality, bleeding (Bleeding Academic Research Consortium—BARC and Thrombolysis in Myocardial Infarction—TIMI non‐CABG definitions), and major adverse cardiac events (MACE) defined as the composite of all‐cause and cardiac death, any myocardial infarction, target vessel revascularization, or any stent thrombosis. Results: Among 58, 879 patients undergoing PCI in the study period, 2, 117 (3.6%) patients (mean age 73 years, 69.7% males, 73.3% acute coronary syndrome) were treated with BMS implantation (2, 353 treated lesions). The rate of BMS implantation progressively decreased from 10.1% (2013) to 0.3% (2017). Main reasons for BMS implantation were: ST‐elevation myocardial infarction (STEMI) (23.1%), advanced age (24.4%), and physician's perception of high‐bleeding risk (34.0%). At a mean follow‐up of 2.2 ± 1.5 years, all‐cause and cardiac mortality were 25.6 and 12.7%, respectively; MACE rate was 35.3%, any bleeding rate was 13.0% (BARC 3–5 bleeding 6.3%, TIMI non‐CABG major bleeding 6.1%). Conclusion: In a large, contemporary, real‐world, multicenter registry, BMS use progressively reduced over the last 5 years. Main reasons for BMS implantation were STEMI, advanced age, and physician's perception of high‐bleeding risk. High rates of mortality and MACE were observed in this real‐world high‐risk population.